China-Russia Cooperation Exchanges in Retrospect and Cultural Communication in Prospect: – Based on the Strategy of Comprehensive Revitalization of Northeast China and Harbin’s Booming Winter Tourism - Zhang, Wanyue (Transactions on Social Science, Education and Humanities Research, 2024)
The year 2024 marks the 75th anniversary of the establishment of diplomatic relations between China and Russia. Over the past ten years, the China-Russian Comprehensive Strategic Partnership of Coordination has become increasingly close and deeply rooted in people’s minds. The paper reviews the exchanges between China and Russia in the areas of political communication, economic cooperation and cultural exchanges since the 18th CPC National Congress (2012), as well as with the guidance of the strategy of Comprehensive Revitalization of Northeast China and under the background of Harbin’s Booming Winter Tourism, Northeast China makes full use of geographic advantages and resource endowments to play the role of "transfer station" and "bridgehead" in China-Russia economic and trade cooperation and cultural exchanges. What’s more, the paper discusses recommendations of Northeast China in terms of expanding the influence of culture and tourism, creating regional brand characteristics, and optimizing the main body, media and activities of external communication, to put forward a Chinese proposal with characteristics of the Northeast region from the perspective of China-Russian friendly exchanges and cross-cultural communication.